Biographical dictionary of evangelicals - Larsen, Timothy, 1967-; Bebbington, David, 1949-; Noll, Mark A., 1946- (Leicester, England ; Downers Grove, Ill. : InterVarsity Press, 2003)
Biographical articles of people characterized by "conversionism, activism, biblicism, and crucicentrism," born in or before 1935, with careers in the "English-speaking world, understood ... as [Great Britain, the United States of America], Canada, Australia, New Zealand, and South Africa"-- Preface.
Includes bibliographical references and indexes.
Keywords: Evangelists -- Biography -- Dictionaries; Evangelicalism -- Biography -- Dictionaries